Fungal fermented palm kernel expeller as feed for black soldier fly larvae in producing protein and biodiesel - Liew, Chin Seng; Wong, Chung Yiin; Abdelfattah, Eman A.; Raksasat, Ratchaprapa; Rawindran, Hemamalini; Lim, Jun Wei; Kiatkittipong, Worapon; Kiatkittipong, Kunlanan; Mohamad, Mardawani; Yek, Peter Nai Yuh; Herma Dina, Setiabudi; Chin, Kui Cheng; et al. (MDPI, 2022)
Being the second-largest country in the production of palm oil, Malaysia has a massive amount of palm kernel expeller (PKE) leftover. For that purpose, black soldier fly larvae (BSFL) are thus employed in this study to valorize the PKE waste. More specifically, this work elucidated the effects of the pre-fermentation of PKE via different amounts of Rhizopus oligosporus to enhance PKE palatability for the feeding of BSFL. The results showed that fermentation successfully enriched the raw PKE and thus contributed to the better growth of BSFL. BSFL grew to be 34% heavier at the optimum inoculum volume of 0.5 mL/10 g dry weight of PKE as compared to the control. Meanwhile, excessive fungal inoculum induced competition between BSFL and R. oligosporus, resulting in a reduction in BSFL weight. Under optimum feeding conditions, BSFL also registered the highest lipid yield (24.7%) and protein yield (44.5%). The biodiesel derived from BSFL lipid had also shown good compliance with the European biodiesel standard EN 14214. The high saturated fatty acid methyl esters (FAMEs) content (C12:0, C14:0, C16:0) in derived biodiesel made it highly oxidatively stable. Lastly, the superior degradation rate of PKE executed by BSFL further underpinned the sustainable conversion process in attaining valuable larval bioproducts.